Investigation of the Presence of Transverse Isotropy in the 3D Baseline Seismic Data from Ketzin, Germany - Mingkhwan Kruachanta (2018)
© 2015 The Authors. In this study, we investigated the presence of transverse isotropy at the Ketzin CO2 pilot storage site, Germany. The anisotropy parameter, eta (Latin small letter Eng), is used as an indicator of anisotropy. Preliminary results show that Latin small letter Eng ranges from -0.2399 to 0.1341, which indicates weak anisotropy. Introducing Latin small letter Eng into the velocity estimation and applying the nonhyperbolic moveout correction resulted in an improvement in the continuity of reflections in the shallow part of the final migrated seismic data.